Argentine entrepreneurial ecosystem: difficulties in the entrepreneurial action of industrial designers - Federico Del Giorgio Solfa; Enrique D´Amico (Revista Cubana de Administración Pública y Empresarial)
Entrepreneurship in Argentina is a complex phenomenon and the entrepreneurial ecosystem is made up of a wide diversity of actors. Among the existing interdisciplinary relationships and practices, the industrial designer is included as a strategic agent in innovation processes. However, the figure of the entrepreneur that has been built by those who promote this form of insertion into the labor market, is loaded with values associated with optimism, creative freedom and personal development, minimizing other negative aspects such as informality, self-exploitation and multifunctional roles that blur the skills of the professional designer. These difficulties of the Argentine entrepreneurial ecosystem are addressed in this article.